Learning Animation Videos with STEM Approach to Improve Students' Problem Solving Ability in Mathematics Subjects in Elementary School - Musriyenti Musriyenti (UM Purwokerto Press, 2023)
This study aims to determine the effect of learning animation videos with the STEM approach to improve students' problem-solving skills in Mathematics in grade IV Elementary School. The data collection instrument in this study was the distribution of online questionnaires in the form of a google form link. The results of this study show that there is a relationship between the use of learning animation videos and students' problem-solving skills on fractions in mathematics in elementary schools. Based on the results of the person correlation test, it shows that there is an influence between the use of learning videos and problemsolving abilities, that is, the correlation result is 0.662. Problem solving ability of students is very necessary so that later students are active in learning activities. One method that can be applied is problem solving skills. opinions that he has and the teacher will assess the opinions of these students. Based on the findings, learning animation videos are suitable for schools with supporting facilities and infrastructure, for example schools that have LCD projectors, because to play learning animation videos, a device is needed and the use of learning animation videos requires teachers to be more creative in adapting animations to the material presented. will be served. Learning animation videos are also suitable for use in subjects such as Literature, Social Studies, Science, PKN, and others.